Liquidity transformation, collateral assets and counterparties - Calebe de Roure; Nick McLaren (Central Bank Review (CBR), 2021)
We investigate if the Bank of England's liquidity facilities encourage some counterparties to participate more than others and if the use of some collateral assets is promoted more than others. Between 2010 and 2016, there was regular usage of two facilities: Indexed Long-Term Repos (ILTR) and the Funding for Lending Scheme (FLS). We show that participation in ILTR is consistent with safe counterparties using the facilities to meet their liquidity needs. Collateral assets used for FLS are less liquid. Riskier and larger institutions are more likely to pre-position collateral in the FLS, but these counterparties do not subsequently draw upon FLS more than others do.
Keywords: E41; E58; G21; G28; 330; Collateral assets; Counterparties; Money demand